Role Of Local Disaster Management Authority For Facing High Tide Disaster At Pacitan Bay, East Java. - oktiyas muzaky Luthfi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2019)
Pacitan Bay is open water directly front on the high seas Indian Ocean, so the Pacitan Bay have many potential threat of strong waves that can cause abrasion or erosion in the coast. Coral reefs damage around the coast of East Java, mainly in the Pacitan can cause the flow of strong wave there is no barrier to reduce the speed of the wave. Green belt in the coastal of Pacitan is limited, so the potential damage to coastal erosion due to strong waves can reach wider. The government needs to do this disaster because effect of erosion